2003
DOI: 10.1002/gea.10084
|View full text |Cite
|
Sign up to set email alerts
|

Geoarchaeological investigations at Studenoe, an Upper Paleolithic site in the Transbaikal Region, Russia

Abstract: In 1998, geoarchaeological research was carried out at the Upper Paleolithic site of Studenoe in the Transbaikal Region of Russia. The site is divided into three loci situated on two terraces overlooking the Chikoi River. Alluvial sediments beneath the oldest terrace (T 2 ) consist of two depositional units. Radiocarbon ages indicate that aggradation of the T 2 fill began before 18,000 yr B.P. Alluvial sediments beneath the lower terrace (T 1 ) range in age from 13,000 to 10,000 yr B.P. and are divided into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…These include 11 sites with 14 C values generated on megafaunal bones not necessarily directly corresponding to the LGM. This is especially true for Studenoe 2, where the single LGM value of c. 18,830 rcbp from layer 4/5 (Buvit et al 2003;Goebel et al 2000;Kuzmin et al 2004a; Table 3) contradicts the general site stratigraphy. The charcoal 14 C value of 17,165 ± 115 rcbp (AA-23657) from the underlying cultural layer 5 (Buvit et al 2004;Goebel et al 2000) does not overlap with the LGM date with ±2r; calibrated ages for these two dates also do not overlap (see Kuzmin et al 2004b).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These include 11 sites with 14 C values generated on megafaunal bones not necessarily directly corresponding to the LGM. This is especially true for Studenoe 2, where the single LGM value of c. 18,830 rcbp from layer 4/5 (Buvit et al 2003;Goebel et al 2000;Kuzmin et al 2004a; Table 3) contradicts the general site stratigraphy. The charcoal 14 C value of 17,165 ± 115 rcbp (AA-23657) from the underlying cultural layer 5 (Buvit et al 2004;Goebel et al 2000) does not overlap with the LGM date with ±2r; calibrated ages for these two dates also do not overlap (see Kuzmin et al 2004b).…”
Section: Discussionmentioning
confidence: 97%
“…Geoarchaeological studies were undertaken by L. D. Bazarova (Tseitlin and Aseev 1982, pp. 68-69) and Buvit (Buvit et al 2003.…”
Section: Studenoementioning
confidence: 98%
“…This was followed by similar research carried out in several other regions across northeast Asia (e.g., Kuznetsov, 1996;Goebel et al, 2000;Goebel, Waters, & Dikova, 2003;Buvit et al, 2003;Buvit, 2008). Results have been used for discussing the adaptive dispersal of modern humans throughout the area (Buvit et al, 2003;Goebel, Waters, & Dikova, 2003), while at the same time demonstrating the difficulties in establishing regional chronologies (Kuznetsov, 1996).…”
Section: Introductionmentioning
confidence: 76%
“…Razgildeeva et al (2013) concluded that the 14 C age for food adhesions at the Studenoe 1 site is older than the 14 C values obtained on charcoal, and the former should be c. 12 000-13 000 calBP. Perhaps, they are not aware of the charcoal 14 C date of c. 11 995 BP (Buvit et al 2003) corresponding to 13 470-14 210 calBP. This value fits perfectly well with the age of the food remains, and in my opinion, the pottery from the Studenoe 1 site can now be securely dated to c. 12 000 BP (centred at c. 13 840 calBP).…”
Section: Transbaikalmentioning
confidence: 99%